(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to shed light on how to reduce the costs of producing electrical energy by using the technology of direct burning of solid waste and investing it in the field of providing environmentally friendly energy in sufficient quantities, reducing the proportion of emissions and pollutants that cause global warming, working to raise the level of production efficiency of electrical energy, and trying to bridge the gap in production companies. Energy in general and at the level of the public company/central region in particular, which in turn contributes to reducing government spending on fuel imports In order to achieve the objectives of the current research, it was applied in the General Company for Electric Power Production / Central Region, based on data for the year 2021, which is one of the formations affiliated with the Iraqi Ministry of Electricity, which includes a number of stations producing energy of various types (steam, diesel, gas), which depend mainly on fuel. fossil in its work.